Unveiling management trends in the public sector: A literature review and research agenda - Santos, M. R. C.; Laureano, R. M. S. (Central European Journal of Public Policy, 2023)
Scholars and practitioners have, for many decades, sought to address management issues related to public sector policies. Thisstudy examines the academic research on this sector focused on these topics by conducting an automated computer analysis of 17,928 documentsindexed in Scopus and published between 1950 and 2021. Six clusters were identified within this literature: economic growth during crises,reforms for the future, human relations, successful practices, partnerships and public banking services. This study thus systematises the lessonslearned over the past decades, thereby contributing to governments’ ability to design public policies to meet future challenges and providingtools for dealing with the current coronavirus disease-19 pandemic.